Anterior cervical decompression and fusion accelerates adjacent segment degeneration: comparison with asymptomatic volunteers in a ten-year magnetic resonance imaging follow-up study - Matsumoto, Morio; Okada, Eijiro; Ichihara, Daisuke; Watanabe, Kota; Chiba, Kazuhiro; Toyama, Yoshiaki; Fujiwara, Hirokazu; Momoshima, Suketaka; Nishiwaki, Yuji; Iwanami, Akio; Ikegami, Takeshi; Takahata, Takeshi; et al. (Spine (Philadelphia, Pa. 1976), 2010)
Prospective 10-year follow-up magnetic resonance imaging (MRI) study of patients who underwent anterior cervical decompression and fusion (ACDF) and healthy control subjects. To clarify the incidence of adjacent segment degeneration during 10 years after ACDF. There have been few studies which investigated incidence of progression of degenerative changes at adjacent segments in patients treated by ACDF comparing with healthy subjects. Sixty-four patients who underwent ACDF (48 males, 16 females, mean age 47.3 years, mean follow-up 12.1 year) and 201 asymptomatic volunteers who underwent MRI in our previous study (113 males, 88 females, mean age; 41.1 year, mean follow-up; 11.7 years) were included in this study. The patients and control subjects underwent follow-up MRI in this study. Following MR findings were evaluated using a numerical grading system from C2-C3-C7-T1: (1) Decrease in signal intensity of disc (DSI), (2) Posterior disc protrusion (PDP), (3) Disc space narrowing, and (4) Foraminal stenosis. When an increase in at least one grade in any of the radiographic parameters was detected between the 2 time points, progression of disc degeneration was judged as present at the level of interest. Progression of DSI was significantly more frequent in ACDF group than in control group at C4-C5, while progression of PDP was significantly more frequent in ACDF group than in control group at all levels except for C5-C6. Progression of disc space narrowing and foraminal stenosis was significantly more frequent in ACDF group at C3-C4 and at C6-C7, respectively. Although both ACDF patients and control subjects demonstrated progression of disc degeneration during 10 years, ACDF patients had significantly higher incidence of progression of disc degeneration at adjacent segments than control subjects, while progression of disc degeneration at adjacent segments was not always related to development of clinical symptoms.